Redefining the Multiple Sclerosis Severity Score (MSSS): The effect of sex and onset phenotype. (November 2020) - Zhou, Yuan; Claflin, Suzi B; Stankovich, Jim; van der Mei, Ingrid; Simpson, Steve; Roxburgh, Richard H; Kalincik, Tomas; Blizzard, Leigh; Lugaresi, Alessandra; Alroughani, Raed; Sajedi, Seyed Aidin; Butzkueven, Helmut; et al.
Background: The Multiple Sclerosis Severity Score (MSSS) is a widely used measure of the disability progression rate. However, the global MSSS may not be the best basis for comparison between all patient groups. Objective: We evaluated sex-specific and onset phenotype–specific MSSS matrices to determine if they were more effective than the global MSSS as a basis for comparison within these subsets. Methods: Using a large international dataset of multiple sclerosis (MS) patient records and the original MSSS algorithm, we constructed global, sex-specific and onset phenotype–specific MSSS matrices. We compared matrices using permutation analysis. Results: Our final dataset included 30, 203 MS cases, with 28.9% males and 6.5% progressive-onset cases. Our global MSSS matrix did not differ from previously published data ( p > 0.05). The progressive-onset-specific matrix differed significantly from the relapsing-onset-specific matrix ( p < 0.001), with lower MSSS attributed to cases with the same Expanded Disability Status Score (EDSS) and disease duration. When evaluated with a simulation, using an onset-specific MSSS improved statistical power in mixed cohorts. There were no significant differences by sex. Conclusion: The differences in the disability accrual rate between progressive- and relapsing-onset MS have a significant effect on MSSS. An onset-specific MSSS should be used when comparing the rate of disability progression among progressive-onset cases and for mixed cohorts.